2011
DOI: 10.1007/s12291-011-0116-4
|View full text |Cite
|
Sign up to set email alerts
|

End Stage Renal Disease, Differential Diagnosis, A Rare Genetic Disorder: Bardet–Biedl Syndrome: Case Report and Review

Abstract: End stage renal disease (ESRD) represents a clinical condition in which there is an irreversible loss of endogenous renal function. Both structural and functional abnormalities of the kidney are associated with increased morbidity, mortality. Bardet-Biedel syndrome (BBS) is one of the rare genetic disorders with prevalence of 1 in 1, 40,000-1 in 1,60,000 worldwide. ESRD in BBS patients is the final stage of the disease, increasing mortality in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Rathi et al [14] described the first case from India with ESRD who was treated with continuous ambulatory peritoneal dialysis (CAPD). Sowjanya et al [2] reported a 16 year old female with ESRD. Prakash [9] reported another 30-yearold patient with BBS who had cysts in the left kidney with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rathi et al [14] described the first case from India with ESRD who was treated with continuous ambulatory peritoneal dialysis (CAPD). Sowjanya et al [2] reported a 16 year old female with ESRD. Prakash [9] reported another 30-yearold patient with BBS who had cysts in the left kidney with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Prakash [9] reported another 30-yearold patient with BBS who had cysts in the left kidney with normal renal function. ESRD in BBS patients has been reported at age range of 4-57 years [2][3][4][5][15][16][17][18][19]. Management of BBS is supportive and includes training and rehabilitation for blind and mentally retarded patients, hearing aids for deafness, and diet and exercise for obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal failure is one of the primary features and a major cause of morbidity and mortality in BBS patients [Imhoff et al, 2010;Sowjanya et al, 2011]. The renal abnormalities are variable but classically manifest with cystic tubular disease and anatomical malformations.…”
Section: Renal Abnormalitiesmentioning
confidence: 99%
“…[1][2][3] Patients with ESRD have significantly increased morbidity and mortality, 4 and should receive a kidney transplant/live on dialysis. 5,6 Patient suffering from ESRD displays enhanced genomic damage, and DNA repair gene polymorphisms may affect DNA repair capacity and modulate susceptibility to ESRD.…”
Section: Introductionmentioning
confidence: 99%